Development of Clinical Rating Criteria for Tests of Lumbopelvic Stability. (29th December 2011) - Perrott, Margaret A.; Pizzari, Tania; Opar, Mark; Cook, Jill
Abstract : Background . Lumbopelvic stability (LPS) is regarded as important for injury prevention, yet there are few reliable or valid tests that can be used in the clinical assessment of LPS. Three dynamic functional tests were identified that assess LPS in multiple planes of motion: dip test (DT), single leg squat (SLS), and runner pose test (RPT). Existing rating criteria for SLS have limited reliability and rating criteria for DT and RPT have not been established. Objective . To develop rating criteria for three clinical tests of LPS. Design . Qualitative research: focus group. Method . A focus group of five expert physiotherapists used qualitative methods to develop rating criteria for the three clinical tests. Results . Detailed rating criteria were established for the three tests. Each key factor considered important for LPS had characteristics described that represented both good and poor LPS. Conclusion . This study established rating criteria that may be used to clinically assess LPS.